Developing health literacy education for tertiary-based health or social care professions students: a scoping review - Helen Wood; Gabrielle Brand; Rhonda Clifford; Kenneth Lee; Samantha Stiles; Liza Seubert (Health Literacy and Communication Open)
Background Despite being a key determinant of health, global health literacy levels remain low for one-third to one-half of the population. Health literacy education is crucial for health or social care professions students during their tertiary degree.Aim To review and describe the development of health literacy education for health or social care professions students.Methods Eleven databases were searched for articles describing developers and the process of development of tertiary-level health literacy education for health or social care professions students. A four-stage screening process was used by two independent authors. Developers were narratively described; development processes were mapped to relevant phases of an established educational design model.Results Forty-six articles were included; most were from the United States. Education was developed by academic staff, health professionals, health literacy experts, librarians, health professions students, PhD students, external stakeholders and project employees; some developers’ roles spanned multiple categories. Articles described elements of zero (n = 1), one (n = 12), two (n = 21) or three (n = 12) phases of the educational design framework during the development process.Discussion This review highlights the need for health literacy education in health and social care professions to be developed using a relevant framework and in consultation with stakeholders such as health consumers. This comprehensive approach will enhance its local relevance to the community and students. The resulting education will empower students with the health literacy knowledge and responsiveness needed to meet the diverse health literacy needs of their community, improving patient outcomes.